Compositional variations in In0.5Ga0.5N nanorods grown by molecular beam epitaxy - Cherns, D.; Webster, R. F.; Novikov, S. V.; Foxon, C. Thomas; Fischer, A. M.; Ponce, F. A.; Haigh, S. J. (IOP Publishing, 2014)
The composition of InxGa1 − xN nanorods grown by molecular beam epitaxy with nominal x = 0.5 has been mapped by electron microscopy using Z-contrast imaging and x-ray microanalysis. This shows a coherent and highly strained core-shell structure with a near atomically sharp boundary between a Ga-rich shell (x∼0.3) and an In-rich core (x∼ 0.7), which itself has In- and Ga-rich platelets alternating along the growth axis. It is proposed that the shell and core regions are lateral and vertical growth sectors, with the core structure determined by spinodal decomposition.